Association of cigarette smoking with serum microRNA expression among middle-aged Japanese adults - Koji Suzuki; Hiroya Yamada; Ayuri Nagura; Koji Ohashi; Hiroaki Ishikawa; Mirai Yamazaki; Yoshitaka Ando; Naohiro Ichino; Keisuke Osakabe; Keiko Sugimoto; Nobuyuki Hamajima; Takashi Inoue (Fujita Medical Journal, 2016)
Objectives: Circulating micro (mi)RNA profiles are influenced by various medical conditions, and miRNAs have been examined as potential biomarkers for cancer, cardiovascular disease, and diabetes. However, few studies have investigated whether circulating miRNAs and cigarette smoking are correlated. Our aim was to determine the association between smoking status and expression of various miRNAs in a Japanese population sample. Methods: We conducted a cross-sectional analysis of 526 subjects (219 men and 307 women) aged 39 years and older who had undergone a health examination at a clinic in Yakumo, Hokkaido in August 2012. We used quantitative real-time polymerase chain reaction to determine serum miRNA expression. We then calculated the odds ratios for elevated serum miRNA levels according to smoking status using never-smokers as the reference group. Results: Expression of lethal (let)-7d, miRNA(miR)-150, miR-192, miR-197 and miR320 was significantly higher in current smokers than in never-smokers. Multivariate logistic regression analyses showed that while current smokers were significantly more likely to have elevated serum levels of miRNA let-7d, miR-21, miR-122, miR-146, miR-150, miR-192, miR-197, and miR320 than never-smokers, former smokers had significantly higher odds of having elevated miR-1, miR-146, miR-150, miR-195, and miR-320 levels in their sera. Conclusions: We found that cigarette smoking is associated with elevated expression of various serum miRNAs. Our results suggest that it is necessary to consider the confounding effect caused by smoking when evaluating expression of serum miRNAs for diagnosing pathological conditions.